Coupled North Atlantic Sub-decadal Variability in CMIP5 Models - Martin, Thomas; Reintges, Annika; Latif, Mojib (Journal of Geophysical Research: Oceans, 2019)
The interaction between the atmosphere, specifically the North Atlantic Oscillation (NAO), and the North Atlantic ocean circulation on sub‐decadal timescale is analyzed in a subset of models participating in the Coupled Model Intercomparison Project phase 5 (CMIP5). From preindustrial control runs of at least 500 years length, we derive anomaly patterns in the atmospheric and ocean circulation and of air‐sea heat exchange. All models simulate a distinct dipolar oceanic overturning anomaly at the sub‐decadal timescale, with centers at 30° N and 55° N. The dipolar overturning anomaly goes along with marked anomalies in the North Atlantic sea surface temperature and gyre circulation. Lag‐regression analyses demonstrate, with relatively small ensemble spread, how the atmosphere and the ocean circulation interact. The dipolar anomalies in the overturning are forced by NAO‐related wind stress curl anomalies. Anomalous surface heat fluxes in concert with anomalous vertical motions drive a meridional dipolar heat content anomaly in the upper ocean, and it is this dipolar heat content anomaly which carries the coupled system from one phase of the sub‐decadal cycle to the other by reversing the tendencies in the overturning circulation. The coupled sub‐decadal variability derived from the CMIP5 models is characterized by three elements: a wind‐driven part steering the dipolar overturning anomaly, surface heat flux anomalies that support a heat build‐up in the subpolar gyre region, and the heat storage memory which is instrumental in the phase reversal of the NAO.